The Summary of Human Resource Management for Language Teaching Organization - Sapto Mei Budiyanto (Jurnal Pendidikan Ilmu Sosial, 2014)
The main target of this writing is to show that HRM (Human Resource Management)has very important and crucial role for enlarging and enriching LTO (LanguageTeaching Organization), therefore, better quality of HRM will be better theLTO’performance. Smart and professional candidate is badly needed in this case, therefore,an accurate and honest selection should be conducted in fair way to get the best result of it.Accurate selection of candidates, cooperation, and understanding among the members ofLTO; from manager, teachers, staffs, up to workers will give a great impact for the bettermentof LTO. Skill and professionalism should be the first priority for running on the LTOprogram. Vision and Mission should be clear and sharp in giving guidance and direction ofthe main target of LTO. This simple writing will guide you, how to find out the best things foryour language teaching organization. If you did it in order, you will find it your qualified andexcellent organization. If everything runs well, LTO will reach up the best achievement.